CMOS Integrated Nanocrystalline SnO2 Gas Sensors for CO Detection. (2016) - Lackner, E.; Krainer, J.; Wimmer-Teubenbacher, R.; Sosada, F.; Gspan, C.; Rohracher, K.; Wachmann, E.; Koeck, A.
Abstract: In this work, we present gas sensors based on nanocrystalline SnO2 ultrathin films, which were integrated on microhotplate chips fabricated by CMOS technology. The gas sensitive films, with a thickness of 50nm, were deposited on the microhotplate by a spray pyrolysis process. The CMOS integrated sensor resistance was significantly decreased in the presence of carbon monoxide. A sensor response of up to 50% is achieved at an operating temperature of 375̊C. The microhotplate chips presented here enable 3D integration of different gas sensing systems by through-silicon-via technology. Such 3D-integrated nanosensors are promising candidates for building smart gas sensor devices for daily life applications.